Countdown to the Year 1000 - McMullan, Kate; Basso, Bill (Edina, Minn. : Spotlight, 2007)
Alarmed by a prophecy that the world will end with the arrival of the year 1000, the students of Dragon Slayers' Academy get some advice from Zack, a boy who has traveled back from 1999.
Originally published: New York : Grosset & Dunlap, 1999.
Keywords: Prophecies -- Fiction; Millennium -- Fiction; End of the world -- Fiction; Dragons -- Fiction; School stories; Time travel -- Fiction